The life and times of Benny Alvarez - Johnson, Peter, 1951- (Harper, an imprint of HarperCollinsPublishers, 2014)
As his English teacher focuses on poetry during the month of October, Benny faces down the smartest girl at school while also navigating his friendships and a difficult family life after his grandfather's multiple strokes.